Model Hubungan Pertukaran Waktu dan Biaya pada Pekerjaan Rangka Atap di Kabupaten Pidie - Rita Zahara; Nurul Malahayati; Fachrurrazi Fachrurrazi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2020)
At the time of construction work, things that can lead to the outcome of the project, such as building, design and giving birth to mobilization. To overcome the necessary acceleration of construction projects. This study examines a large number of additional acceleration costs per day, aimed at creating Time Cost Trade off (TCTO) models in Pidie District. The time trade cost off model will be developed from questionnaire distribution data to directors, managers, project estimators domiciled in Pidie District. In addition to questionnaires, this study also uses secondary data that is cost budget plan (RAB) obtained from respondents. The analysis used in this research is simple linear regression analysis. The resulting model for lightweight steel roof truss work is c = 35.170.497,87-640.612,35d with and duration of accident (Dc) is 4 days. Therefore, the maximum acceleration that can be made is 6 days (60% of the normal duration) and the maximum additional charge of 9.33% of the normal cost with an additional cost per day (slope) is 2.33% of the normal cost.